IMPLEMENTATION GAME BASED LEARNING MODEL IN BUILDING STUDENT SOCIAL COMPETENCE - qotrunnada, Nadiyah; Sari, Ulfi Andrian (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
The purpose of this study is to determine each stage in the game-based learning model in the form of giving rules, goals, interactions, challenges and results that are able to build social competence in the form of self-control, discipline, empathy, assertiveness, freedom of friends, responsibility, and cooperation. Game based learning learning model as a solution to able build students' social competence. This study uses a qualitative approach with a descriptive type. Data were collected through observation, interviews and documentation. Observations were made at MTs Bahrul Ulum Tajinan and interviews were conducted with social science teachers and eighth grade students. The data analysis technique uses interactive analysis by Miles, Huberman and Saldana which consists of collecting data by simplifying the data collected so that it can emphasize the focus of the research, presenting data in the form of charts that help make the data more selective and simple, then verifying the data or conclusions on the data collected. has been shown. The results showed that the game-based learning model was able to build students' social competence. The stage of giving rules is able to foster self-control and discipline. At the stage of giving goals and interactions, it is able to foster an attitude of responsibility, assertiveness and freedom to make friends. Through the stages of competition and challenges are able to build an attitude of cooperation. Part of results and feedback can able to build an attitude of empathy in students.